1998
DOI: 10.1051/analusis:1998124
|View full text |Cite
|
Sign up to set email alerts
|

Headspace GC-SCD monitoring of low volatile sulfur compounds during fermentation and in wine

Abstract: Abstract. Adsorptive accumulation in stripping voltammetry has been applied for trace measurements of the cancerostatic drug actinomycin-C1 (ACT). Accumulation is achieved by controlled adsorption of ACT film on the hanging mercury drop electrode (HMDE). The cathodic stripping response was evaluated with respect to accumulation time, concentration dependence, solution conditions and other variables. The limit of detection after 5 minutes preconcentration is 1 µg L −1 (8 × l0 −10 M). The effects of possible int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 11 publications
8
28
2
Order By: Relevance
“…Static and dynamic HS extractions have been shown to be less sensitive and less selective methods for headspace analysis when compared to SPME (Kataoka et al 2000). However, in some cases, particularly for highly volatile compounds, static HS methods can be highly sensitive, as when detection limits of 0.1 to 3 ug/L for low molecular weight sulfur compounds in wines were obtained (e.g., H 2 S and DMS) (Rauhut et al 1998), similar to those reported using other approaches, including HS-SPME-GC (Herszage and Ebeler 2011).…”
Section: Sample Preservation and Preparationsupporting
confidence: 70%
“…Static and dynamic HS extractions have been shown to be less sensitive and less selective methods for headspace analysis when compared to SPME (Kataoka et al 2000). However, in some cases, particularly for highly volatile compounds, static HS methods can be highly sensitive, as when detection limits of 0.1 to 3 ug/L for low molecular weight sulfur compounds in wines were obtained (e.g., H 2 S and DMS) (Rauhut et al 1998), similar to those reported using other approaches, including HS-SPME-GC (Herszage and Ebeler 2011).…”
Section: Sample Preservation and Preparationsupporting
confidence: 70%
“…They are characterized by some fruity aromas, like cassis [45], grapefruit [46], passion fruit [47] and guava [48]. The impact of sulfur compounds on wine aroma has been updated in literature and the varietal character is affected by several of these molecules if their concentration is close to the perception threshold [22, 49,50]. 3MH and 3MHA have olfactory perception thresholds of 60 and 4 ng/L, respectively and they are responsible for passion fruit-like and grapefruit-like olfactory notes [11].…”
Section: Varietal Thiolsmentioning
confidence: 99%
“…The detected compounds, many of them containing sulfur, correlated well with the odorants identified in sensory analysis. Low levels of volatile sulfur compounds during fermentation and in wine were measured by Rauhut et al [78] with an automatic headspace injection sampler and a cooled injection system coupled with GC-SCD. Prentice et al [79] developed a method incorporating purge-and-trap, oncolumn injection, and SCD detection to measure methional, which was believed to be a precursor of certain polysulfides, significant flavor congeners in Scotch whiskey.…”
Section: Characterization Of Beers and Other Alcoholic Beveragesmentioning
confidence: 99%